2009
DOI: 10.3168/jds.2008-1904
|View full text |Cite
|
Sign up to set email alerts
|

Modeling milk urea of Walloon dairy cows in management perspectives

Abstract: The aim of this study was to develop an adapted random regression test-day model for milk urea (MU) and to study the possibility of using predictions and solutions given by the model for management purposes. Data included 607,416 MU test-day records of firstlactation cows from 632 dairy herds in the Walloon Region of Belgium. Several advanced features were used. First, to detect the herd influence, the classical herd × test-day effect was split into 3 new effects: a fixed herd × year effect, a fixed herd × m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
37
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 25 publications
16
37
1
3
Order By: Relevance
“…) between 12 and 21 mg · dl −1 (Johnson and Young, 2003;Wattiaux et al, 2005;Stoop et al, 2007;Bastin et al, 2009) but close to levels observed in Canadian (Miglior et al, 2006) and Israeli (Ramirez et al, 2007) populations. The coefficient of variation was very high and stable for all test days, ranging from 44% to 48%.…”
Section: Level Of Mu Concentration and Effect Of Stage Of Lactationsupporting
confidence: 72%
See 4 more Smart Citations
“…) between 12 and 21 mg · dl −1 (Johnson and Young, 2003;Wattiaux et al, 2005;Stoop et al, 2007;Bastin et al, 2009) but close to levels observed in Canadian (Miglior et al, 2006) and Israeli (Ramirez et al, 2007) populations. The coefficient of variation was very high and stable for all test days, ranging from 44% to 48%.…”
Section: Level Of Mu Concentration and Effect Of Stage Of Lactationsupporting
confidence: 72%
“…The lowest MU was observed in winter months (192.2 mg · l −1 in January) . There is no consistent pattern in MU changes between months in the studies of different authors, but they generally report that the greatest concentration can be observed during the summer months (Godden et al, 2001;Arunvipas et al, 2003;Hojman et al, 2004;Wattiaux et al, 2005;Bastin et al, 2009). Only in the Canadian population were low MU concentrations observed not only during the winter but also, for example, in June (Arunvipas et al, 2003;Miglior et al, 2007).…”
Section: Effect Of Month and Temperaturementioning
confidence: 93%
See 3 more Smart Citations